Factors Affecting the Intention to Use E-Wallets during the COVID-19 Pandemic - Kelvin Lee Yong Ming; Mohamad Jais (Gadjah Mada International Journal of Business, 2022)
The COVID-19 pandemic has reshaped the lifestyle of Malaysians. The government has introduced various incentives to encourage contactless transactions. Malaysia has also expe- rienced a spike in e-wallet transactions during the COVID-19 pandemic. However, there is no consensus on the reasons behind the rapid increase in the usage of e-wallets. This study aims to fill a knowledge gap by incorporating government support, the perceived risk, and social influence as the potential factors affecting the use of e-wallets. Survey data were collated from 598 respondents using Google Forms and analyzed using covariance-based structural equation modeling (CB-SEM). The findings confirm that perceived usefulness, government support, the perceived risk, and social influence are positively related to the attitude toward the usage of e-wallets. This attitude is also positively related with the user’s intention of using the wallets. The outcomes of this study may assist policymakers to devise effective strategies that are able to capture the users’ intentions to use e-wallets during the COVID-19 pandemic. This study also recommends that the government increases the incentives to speed up the formation of a cash- less society. The related organizations should also enhance public awareness on the usefulness of e-wallets in preventing virus transmission.